2016
DOI: 10.1007/s10147-016-1059-9
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic and obstetric outcomes and complications during pregnancy after fertility-sparing abdominal trachelectomy for cervical cancer: a retrospective review

Abstract: Our data indicate that the oncologic outcome was excellent but infertility treatment was necessary to achieve the majority of conceptions. Additionally, preterm premature rupture of the membranes and premature delivery were frequently observed. An improved pregnancy rate and prevention of complications during pregnancy are issues that should be addressed in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
3
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 19 publications
2
65
3
2
Order By: Relevance
“…Is RT also practical for pregnant patients with early invasive uterine cervical cancer? Not a few institutes in Japan have started to perform RT for patients with early invasive uterine cervical cancer who desire the preservation of fertility . Their oncological results seem to be as good as for radical hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Is RT also practical for pregnant patients with early invasive uterine cervical cancer? Not a few institutes in Japan have started to perform RT for patients with early invasive uterine cervical cancer who desire the preservation of fertility . Their oncological results seem to be as good as for radical hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The cervical incision line was 5-10 mm below the internal os, as determined by ultrasonography; intraoperative frozen section at 5 mm from the upper cervical margin was performed to verify the absence of tumor. Trachelectomy was not performed when the SLN was positive for metastasis [8]. Patients who did not meet the above criteria underwent hysterectomy.…”
Section: Surgical Technique and Follow-upmentioning
confidence: 99%
“…Okugawa et al reported a successful pregnancy rate of 25% post-trachelectomy in a series of 151 patients 4. To date, this procedure has only been performed in benign symptomatic cervical lesions in three patients 15.…”
Section: Discussionmentioning
confidence: 99%
“…Radical abdominal trachelectomy has been described in the management of selected premenopausal patients with early cervical cancer in an attempt to maintain reproductive potential 4. Reported rates of successful conception post trachelectomy range from 30% to 66% 4–6.…”
Section: Introductionmentioning
confidence: 99%